Irina Serebrianska. Language imeg of education as a valuable attribute of the ukrainian language world picture - Irina Serebrianska (Philological Treatises, 2020)
The article is devoted to the actual fragment of the national language consciousness – the language image of education in the context of dynamic processes in the modern sphere of education. The views of domestic and 94 «Філологічні трактати», Том 10, № 1 ’ 2018 foreign scientists on the linguistic world picture are systematized here, the place of the language image of education is determined according to the value orientations in society and the personality of the speaker. It is determined that the image of education in the Ukrainian language is constructed with the help of a unique combination of terms with expressive words, which are a manifestation of individual and authorial views and, at the same time, a national outlook, as well as linguistic searches of speakers. The language image of education involves the language implementation of education concept, which are the basis for it. It is a kind of modeling of educational reality through language means. Each speaker, social group, nation, under the influence of extra linguistic factors, forms its own language image, which integrates into the system of language and aesthetic signs of Ukrainian culture. The language image of education accumulates all the meanings of lexical units and their combinations representing this sphere in the language.